Evaluating department chairs’ effectiveness using faculty ratings - Middendorf, B. Jan (Kansas State University, 2009)
This study examined relationships between faculty perceptions of their academic department chair’s overall effectiveness and their ratings of his/her personal characteristics and administrative methods. The experimenter analyzed secondary data obtained from the Individual Development and Educational Assessment (IDEA) Center’s Feedback for Department Chairs system. Data came from 604 department chairs and their corresponding 9,125 faculty members across the years 2003 to 2007. Faculty completed the 70-item Faculty Perceptions of Department Head/Chair Survey, and their department chair responded to the 30-item Department Head/Chair Information Form. Exploratory factor analysis (EFA) of department chair ratings revealed three underlying dimensions of administrative responsibilities, ranked in order of importance: Departmental Operations, Faculty Enhancement, and Research and Assessment. EFAs of faculty ratings determined one factor explained the department chair’s personal characteristics—Flexibility/Adaptability—and one factor explained the department chair’s performance of administrative methods—Communication and Coordination. Items with high component matrix coefficients were summed to produce scales with high reliability for each factor. Multiple regression analysis indicated that faculty ratings of the department chair’s Flexibility/Adaptability and Communication and Coordination explained 83% of the variance in their ratings of the department chair’s overall effectiveness (p < .001). Ratings on Communication and Coordination explained the most variance. Faculty ratings of the department chair’s performance of administrative responsibilities also explained 83% of the variance in their ratings of the chair’s overall effectiveness (p < .001). Faculty Enhancement showed the strongest relationship. The findings help to explain the underlying dimensions of the academic department chair’s effectiveness and the role of faculty ratings in evaluation.
Keywords: Department Chair; Evaluation; Department Head; Performance; Higher Education; Faculty Perceptions; Education, Administration (0514); Education, Curriculum and Instruction (0727); Education, Higher (0745)